Generation of Z: split of traditions or code conversion of culture - Danilov, Alexander N.; Grishchenko, Zhanna M.; Scholkova, Tatiana V. (Journal of the Belarusian State University. Sociology, 2019)
In the center of research attention – modern generation of students. Actual tendencies in the student’s environment are considered and the hypothesis of split in generation of Z and alienation of its solid part from traditional standard valuable model is made. In parallel it is about metodiko-procedural problems of modern sociology and strengthening of its sensitivity to measurement of sense which are put by modern youth in the interpretation of basic values.
Keywords: the generation of Z; a total anomy; total demoralization; intra generational split; traditional standard and valuable model; sensitivity of tools meant and meaning meanings; a culture code